An Analysis of Quantity Maxim Violation in Movie Richard Kletter & Michele Samit Stolen by My Mother: Kamiyah Mobley (2020) - Lusi Adelia Herman; Leni Marlina (English Language and Literature, 2022)
Inability to reach the effectiveness in using maxim makes it turns into misunderstanding of communication.  It is called violation of maxim. This study is aimed to seek quantity maxim violation performed by characters in Richard Kletter and Michele Samit’s movie Stolen by My Mother: Kamiyah Mobley (2020) This research was descriptive qualitative analysis. The data were collected from utterances of the characters and then were analyzed by using Grice’s theory (1975).  The result of this study shows that all characters violated the quantity maxim in 18 times, with different categories of violation.  The most dominant category of quantity maxim violation is when the speakers talk too much and give too short contribution in conversation (55%). The other categories quantity maxim violation in the movie are Uninformative (27%) and Circumlocution (16%). Meanwhile, another category is Repeat Certain Word, it does not exist in the movie. Cooperative Principle, Quantity Maxim, Violation of Maxim